Statistical distribution of the signal phase of VLF-range at sudden ionospheric disturbances - V.I. Nesterov (Физика волновых процессов и радиотехнические системы, 2016)
Influence of sudden ionospheric disturbances on the phase of the accepted signal is considered. Experimental data are obtained on receptions of signal phases by the radio navigational system Omega (frequency range from 10 to 14 kHz) with respect to a reference generator of a secondary standard of time and frequency. Routes of various length and orientation. It is shown that the deviation of the phase of the accepted signal obeys to Poissons distribution.